Non-indigenous amphipods and mysids in coastal food webs of eastern Baltic Sea estuaries. (6th June 2016) - Berezina, Nadezhda A.; Razinkovas-Baziukas, Arturas; Tiunov, Alexei V.
Abstract : The study analyses the role of non-indigenous invertebrates in the food webs of two eutrophic brackish estuarine ecosystems of the Baltic Sea: the Neva River estuary and the Curonian Lagoon, with the aim of clarifying several questions such as what trophic levels were occupied by newly established species (mainly amphipods and mysids) and whether they can affect the native benthic invertebrates as a result of their possible carnivorous nature. Stable isotope analysis (δ 15 N values) and gut contents analysis of field-collected specimens were used to estimate trophic level and trophic links of the newly established malacostracan crustaceans, while their consumption rates when feeding as carnivores were measured experimentally. The δ 15 N analysis allocated four trophic levels (TL) in the coastal food webs of both studied ecosystems with the lowest δ 15 N (2–4‰) for detritus and algae and the highest for fish (12–14‰). Through their high abundance, non-indigenous crustaceans ( Pontogammarus robustoides, Gmelinoides fasciatus, Obessogammarus crassus, Gammarus tigrinus, Limnomysis benedeni and Paramysis lacustris ) have become important members of food chains of the studied ecosystems. Their trophic position varied significantly within species during ontogenesis. This suggests that they turned from being typically detritivores/plantivorous (TL 2–2.4) at juvenile stages to omnivores (2.5–3) or to carnivores (>3) as adults. Assessment of the predation pressure by the adult amphipods on other coexisting invertebrates (in the example of the Neva Estuary) showed a low or medium impact, depending on species of predator and productivity of its potential prey organisms.